2022
DOI: 10.1039/d1tc04286f
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline organic thin films for crystalline OLEDs (I): orientation of phenanthroimidazole derivatives

Abstract: Compared to traditional organic light-emitting diodes (OLEDs) based on amorphous thin films, crystalline OLEDs possess promising advantages in developing advanced display technologies, such as longer life time and lower driving...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…2E and fig. S3A, respectively, indicating their crystallinity nature, and are consistent with the previous report ( 24 , 30 , 31 ). The grazing incident wide-angle x-ray diffraction (GIWAXD) can be carried out to investigate the crystal structure ( 18 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2E and fig. S3A, respectively, indicating their crystallinity nature, and are consistent with the previous report ( 24 , 30 , 31 ). The grazing incident wide-angle x-ray diffraction (GIWAXD) can be carried out to investigate the crystal structure ( 18 ).…”
Section: Resultssupporting
confidence: 92%
“…The grazing incident wide-angle x-ray diffraction (GIWAXD) can be carried out to investigate the crystal structure ( 18 ). Figure S3B shows the GIWAXD images of 2FPPICz crystalline thin film with annotated ( hkl ) parameters according to ( 31 ), indicating that 2FPPICz CHM is composed of polycrystal with well-crystallinity nature. The out-of-plane XRD patterns of BP1T (6 nm)/2FPPICz (5 nm)/CHM-HENA-D (20 nm) are consistent with BP1T (6 nm)/2FPPICz (25 nm), and no other diffraction peak appears ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been confirmed that the weak epitaxy growth (WEG) of 2FPPICz crystalline thin films can be applied on surfaces of smooth amorphous substrates, and their crystal structures are consistent for either PEDOT: PSS or Si/SiO 2 substrate. [ 15 , 39 , 40 ] Thus, the crystalline thin films were prepared on Si/SiO 2 substrate by WEG method, [ 41 , 42 ] to facilitate the analysis and investigation on the crystalline EML morphologies. More than two monolayers BP1T (less than three layers) were first deposited on the Si/SiO 2 substrate to form a continuous crystalline thin film at substrate temperature 102 °C, acting as an inducing layer for the subsequent epitaxy growth of crystalline thin films.…”
Section: Resultsmentioning
confidence: 99%
“…The BP1T and 2FPPICz crystal structures have been studied in the previous reports. [ 14 , 15 , 40 ] (002), (004), and (006) planes of BP1T crystalline thin film and (‐202) plane of 2FPPICz crystalline thin film have been marked at their corresponding peaks, respectively. The XRD patterns of BP1T/2FPPICz/CHM‐HES‐D are consistent with BP1T/2FPPICz and no new diffraction peak appears.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in concentration may also alter the crystallinity and the thin film morphology of composite materials. [80][81][82][83][84] Furthermore, higher doping concentrations of emitters may lead to nonradiative decay of excitons due to the Auger recombination. 85,86 We have also observed the effects of doping concentration on EL spectra of these devices.…”
Section: Electroluminescence Studiesmentioning
confidence: 99%